Coğrafi bilgi sistemlerine yönelik internet uygulamaları ve yazılım geliştirme - Karaş, İsmail Rakıp (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 2001)
Mekana dayalı verilerin yönetim ve organizasyonu "Coğrafi Bilgi Sistemleri nin konusunu oluşturmaktadır. CBS'nin B'si verilerden elde edilir. Dolayısı ile bilgiyi oluşturan veri olmadan bir bilgi sisteminin varlığından söz edilemez. Buna karşılık bir CBS kurulumunda en çok zaman alan, külfetli, pahalı ve rutin aşama verilerin toplanmasıdır. Bazı araştırmalara göre, bir CBS için veri toplamanın toplam maliyete oranı %60-80 düzeyindedir. Bu yüzden bir CBS'nin ihtiyacı olan veriyi ilk elden, en baştan toplamak yerine, mümkün olduğunca, halihazırdaki verilerinden ve o veriye sahip olan başka kaynaklardan elde etmek ve bunları, söz konusu CBS formatına dönüştürmek çok daha ekonomik, hızlı ve akılcı bir yöntemdir. Bunun yolu ise, dönüştürme işlemlerini otomatik olarak yapacak veri çevirici yazılımlar üretmektir. Kurulacağı ortamın, her bir alt biriminde devam eden hizmetlere yönelik, uygulama programlarının geliştirilmesi CBS'nin gereklerindendir. Kullanıcıların sadece kendi mesleklerini bildikleri ve birer "uç kullanıcı" oldukları gözönüne alınarak, Türkçe, anlaşılır ve kullanımı kolay ara yüzlerin tasarlanması, kurulacak sistemin en önemli aşamalanndandır. Bunlar gerçekleştiği ölçüde sistem mükemmele yaklaşacak, kullanılabilirliği artacaktır. Bu noktadan hareketle gerçekleştirilen, bir CBS'nin en önemli ayağı olan "veri elde etme ve veri dönüştürme" işlemlerine yönelik uygulamalar ile, KB S organizasyonlarında kullanılmak üzere geliştirilen otomasyon yazılımları ve internet üzerinden sunulması bu tez bünyesinde yapılan çalışmaların konusunu oluşturmaktadır.

Management and organization of spatial data values form maia topics öf Geographic Information System (GIS). The result of many research works hajr shown that data gathering work is the most time consuming, laborious, expensive and routine one, and its cost covers 60% - 80% of the whole GIS' s cost. In Turkey and elsewhere, some computer programs have been used to carry out the computational and graphical side of the mapping work without any idea of their contribution to a GIS, and outputs of these programs have been kept in digital files. On the other hand, some activities of the municipalities and the government offices have been carried out with the use of computer programs, and the outcomes are kept in digital files or printed forms. That means, some of the data for GIS already exist in some way or another. Therefore, instead of trying to produce all GIS data from the beginning, converting the existing digital files which maybe at random format into a standard format or recognizing characters of the printed text files in digital forms will be a big support to establish GIS. Throughout the years much focus has been placed on developing AM/FM/GIS software packages and various techniques for data conversion and maximing its quality. Although data is undoubtedly the foundation-stone of an AM/FM/GIS, it is not possible to judge the success of the whole system by its data quality and design. The eventual success of the system will be measured with its ease of use and presentation through applications. In competitive business environment, software developers face the urgent need to automate engineering, administrative and public relations activities in order to make the system easy and user-friendly. One of the most time consuming and much care needed applications or activities at municipalities and similar organizations is the preparation of application plans showing size and boundaries of a parcel and/or boundaries of building areas. This thesis examines how these activities are being carried out at above mentioned organizations in Turkey, and possible mathematical problems to be faces when developing Application Programs related to this. And this thesis, present some computer programs which converts data files from any given format to a standard format was developed.
Software development and internet applications for geographic information systems
Keywords: Jeodezi ve Fotogrametri; Geodesy and Photogrammetry